1991
DOI: 10.1001/jama.1991.03470050070025
|View full text |Cite
|
Sign up to set email alerts
|

The Environment and the Lung

Abstract: The focus of public health concern and research in regard to environmental lung diseases has changed across the century. Illustrative agents include radon, indoor asbestos, environmental tobacco smoke, acidic aerosols, and oxidant gases. Tremendous progress has been made in understanding and preventing environmental lung diseases. However, we remain concerned about adverse consequences of breathing polluted outdoor and indoor air. In the persistent concerns about adverse effects of polluted air on the lung, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Particles w10 mm are usually removed at the upper airways, whereas those v10 mm (i.e. RSP) may be deposited in the smaller airways and alveoli [16]. Recently, several studies have found strong associations between outdoor RSP levels and mortality and morbidity, especially in the elderly [17][18].…”
Section: Health Effects Of Respirable Suspended Particles Nitrogen Dmentioning
confidence: 99%
“…Particles w10 mm are usually removed at the upper airways, whereas those v10 mm (i.e. RSP) may be deposited in the smaller airways and alveoli [16]. Recently, several studies have found strong associations between outdoor RSP levels and mortality and morbidity, especially in the elderly [17][18].…”
Section: Health Effects Of Respirable Suspended Particles Nitrogen Dmentioning
confidence: 99%
“…The cellular responses are provided by several types of immunocompetent cells, including macrophages, mast cells, eosinophils, neutrophils, and lymphocytes (Kolopp-Sarda et al, 1994;Pabst and Gehrke, 1992;Pabst and Tschernig, 1995). In normal conditions, as in other mucosal areas, nonspecific and specific immune responses in the lung are efficient and noninflammatory (Brandtzaeg, 1996;Jeffery and Corrin, 1984;Samet and Utell, 1991), and only small numbers of lymphocytes are present in lung alveoli. In respiratory diseases, inappropriate or ill-regulated immune responses may develop, involving the bronchi, lung parenchyma, and, in some instances, alveoli (Agostini et al, 1993).…”
mentioning
confidence: 99%
“…AM J RESPIR CRIT CARE MED 1995;152:1932-9. Many studies have been conducted on the health effects of inhalable particulate matter (PMIO) pollution. These particles are of concern because they can penetrate into the lower airways where they can cause lung injury, whereas particles with an aerodynamic diameter greater than 10 11m are to a large extent removed in the upper airways (1). The U.S. Federal air quality standard for PMlO is a 24-h average of 150 ug/m", not to be exceeded more than once a year.…”
mentioning
confidence: 99%